Anterograde‐propagation of axonal degeneration in the visual system of wlds mice characterized by diffusion tensor imaging. Issue 2 (4th July 2016) - Sun, Shu‐Wei; Nishioka, Christopher; Chung, Chen‐Fang; Park, JoAnn; Liang, Hsiao‐Fang
Abstract : Purpose: To evaluate the feasibility of using diffusion tensor imaging (DTI) to characterize the temporospatial profile of axonal degeneration and its relation to blood–brain barrier (BBB) permeability. Materials and Methods: Longitudinal DTI was performed in Wallerian degeneration slow (WldS) mice following retinal ischemia. In parallel, gadolinium (Gd)‐enhanced T 1 ‐weighted imaging (Gd‐ T 1 WI) was performed to evaluate BBB permeability in white matter during axonal degeneration. To confirm the in vivo findings, immunohistochemistry using SMI‐31 and myelin basic protein (MBP) was performed to examine the axons and myelin, respectively, and Evans blue was used to evaluate the permeability of the BBB. Results: Reduced axial diffusivity was found in the optic nerve (ON, –15%, P = 0.0063) 1 week and optic tact (OT, –18%, P = 0.0077) 2 weeks after retinal ischemia, which were respectively associated with an 11% ( P = 0.0116) and 25% ( P = 0.0001) axonal loss. Increased radial diffusivity was found 1–2 weeks after the colocated decrease of axial diffusivity (35% increase, P = 0.0388 in the ON at week 2 and an 80% increase, P = 0.0015 in the OT at week 4). No significant changes were observed using Gd‐ T 1 WI ( P = 0.13–0.75), although an approximately 1‐fold increase in Evans blue staining intensity was found in the injured ON and OT starting 1 week after retinal ischemia. Conclusion: We demonstrated the utility of DTI to characterize anterograde‐propagating axonal degeneration through the ON and OT following retinal damage. Evans blue staining revealed serum albumin accumulation at injured sites, although there was no BBB leakage detectable using Gd‐ T 1 WI. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:482–491.